Innovation as a Mediator of Entrepreneurial Characteristics on Business Success in MSMEs - Asepta, Uki Yonda; Sudarmiatin; Ludi Wishnu Wardhana; Krismi Budi Sienatra (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
This research aims to determine the extent to which entrepreneurial characteristics influence business success through innovation. This type of research is explanatory with a quantitative approach. The population in focus is the MSME (Micro, Small, and Medium Enterprises) actors in Malang City. A total of 97 MSME actors were selected as samples using the purposive sampling technique. Data collection was carried out using questionnaires distributed via Google Forms, and the results were analyzed using path analysis. The results of the study indicate that entrepreneurial characteristics influence business success through innovation.